2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6638621
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stream transmission in MIMO-FBMC systems

Abstract: This paper addresses the design of MIMO precoding and decoding techniques for the filter bank multicarrier (FBMC) modulation. Existing solutions give satisfactory performance in scenarios with high coherence bandwidth channels. With the aim of increasing the robustness against the channel frequency selectivity, we have rethought the problem, which results in a new subband processing. Simulation-based results show that the proposed solution can achieve similar bit error rates as the OFDMsolution, while the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Previous works in the literature have concluded that if no CP is transmitted, then the MIMO techniques originally designed for OFDM can be successfully applied to FBMC/OQAM only in high coherence bandwidth channels [4]. The authors in [4] show that robustness against multipath fading is provided to a higher extent assuming that the channel frequency response (CFR) is flat at the subcarrier level, while it varies on adjacent subcarriers.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous works in the literature have concluded that if no CP is transmitted, then the MIMO techniques originally designed for OFDM can be successfully applied to FBMC/OQAM only in high coherence bandwidth channels [4]. The authors in [4] show that robustness against multipath fading is provided to a higher extent assuming that the channel frequency response (CFR) is flat at the subcarrier level, while it varies on adjacent subcarriers.…”
Section: Introductionmentioning
confidence: 96%
“…The experimental validation conducted in this paper reveals that the coordinated beamforming performs close to OFDM and clearly improves [4]- [6]. The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations